2014
DOI: 10.1130/b30954.1
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric budget and grain-size fractionation of a geological sediment routing system: Eocene Escanilla Formation, south-central Pyrenees

Abstract: The supply of sediment and its characteristic grain-size mix are key controls on depositional facies and stratigraphic architectures in sedimentary basins. Consequently, constraints on sediment caliber, budgets, and fl uxes are a prerequisite for effective stratigraphic prediction. Here, we investigate a mid-to late Eocene (41.6-33.9 Ma) sediment routing system in the Spanish Pyrenees. We derive a full volumetric sediment budget, weighted for grain-size fractions, partitioned between terrestrial and marine dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
79
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(83 citation statements)
references
References 61 publications
4
79
0
Order By: Relevance
“…This issue is pertinent because within sedimentary basins, a change in the erosional dynamics upstream could be recorded by changes in the total sediment volumes stored in sedimentary basins (e.g. Allen et al, 2013;Michael et al, 2014), in sediment delivery or sediment accumulation rates linked to landscape response times (Foreman et al, 2012;Armitage et al, 2015), and/or in the grain sizes deposited as a function of sediment flux output (Paola et al, 1992;Armitage et al, 2011;Whittaker et al, 2011;D'Arcy et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This issue is pertinent because within sedimentary basins, a change in the erosional dynamics upstream could be recorded by changes in the total sediment volumes stored in sedimentary basins (e.g. Allen et al, 2013;Michael et al, 2014), in sediment delivery or sediment accumulation rates linked to landscape response times (Foreman et al, 2012;Armitage et al, 2015), and/or in the grain sizes deposited as a function of sediment flux output (Paola et al, 1992;Armitage et al, 2011;Whittaker et al, 2011;D'Arcy et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Allen et al, 2013;Michael et al, 2014); in sediment delivery or sediment accumulation rates linked to landscape response times (Foreman et al, 2012;Armitage et al, 2015) and/or in the grain-sizes deposited as a function of sediment flux output (Paola et al, 1992;Armitage et al, 2011;5 Whittaker et al, 2011;D'Arcy et al, 2016). Furthermore, laboratory scale experiments have demonstrated that within a physical system of erosion dirven by the surface flow of water, there is a clear response time for the system to recover to steady state after a perturbation Crave, 2003, 2006;Singh et al, 2015).…”
mentioning
confidence: 99%
“…Sediment was transported westwards through the Pyrenean pro-wedge-top region towards an ocean in the Biscay area, and the routing system is therefore distinct from coeval sediment routing systems sourced in the eastern Pyrenees that dispersed sediment into the northeastern Ebro pro-foreland basin (Michael et al 2013). Although there are substantial thicknesses of mid-to upper Eocene sedimentary rocks in the eastern Ebro Basin (Sinclair et al 2005), this region was part of a different, though coeval, sediment routing system to the Escanilla, and was supplied with sediment from feeder systems in the eastern Pyrenees, Catalanides and Iberian chain (Michael et al 2013(Michael et al , 2014.…”
Section: The Escanilla Palaeo-sediment Routing Systemmentioning
confidence: 96%
“…2), occupying a total time span of 7.7 myr. The recognition and mapping of these time intervals is based on bio-and magnetostratigraphy (Beamud et al 2003(Beamud et al , 2010Beamud 2013) backed up by changes in provenance data and sedimentology (Michael 2013), and has been explained in greater detail elsewhere (Michael et al 2013(Michael et al , 2014.…”
Section: The Escanilla Palaeo-sediment Routing Systemmentioning
confidence: 99%
See 1 more Smart Citation